Pengaruh Keberadaan Universitas Haluoleo Terhadap Perubahan Tata Guna Lahan Di Kawasan Andonuohu Kota Kendari - Afriani Amiruddin (Jurnal Wilayah dan Lingkungan, 2014)
University provides educational services for people in a country. The existence of the university may indirectly affect the development of a region marked by numerous changes in land use. A change in land use can also be caused by a concentration of activity in a region. Haluoleo University is a public university located at Andonuohu Kendari (South East Sulawesi). In a region of Kendari, Andonuohu serves as a center of education. Dense population in this area due to the existence of this university can attract people outside of Kendari who want to continue their education at the university. This study purposed to determine the effect of the presence of the university to changes in surrounding land use. This study will be conducted several analyzes in which to perform analyzes using multiple variables are the type of land use, land use and size distribution of land use. The analysis used in this study is the analysis of the emerging system of activities, analysis of the relationship between activity system and analyzes land use change land use changes that occur due to the emergence of system activity. Analysis technique used is descriptive qualitative. The existence of the university system resulted in many activities that support the existence of private universities such as activities, economic, social and leisure travelers. System activity caused most of the land surrounding the university have that implicates changes in land up. Changes in land use occurs which is the number of green open space, open land and farms being turned into residential land and trade and services. However, changes in land which has resulted in physical changes toward a less well as the establishment of several trade and some irregular settlements. This system of activities that appear to have the main goal is to meet the needs of students so can be concluded that the emergence of a wide range of activities is a result of the presence of Haluoleo University. The advent of the existing system of activity can bring huge profits and can indirectly increase the region's economy. The existence of this university have an impact on land use change, where change of land that looks like a rapidly growing field of trade and service activities, recreation and support as many area shops along the main road to the campus that is the way MT. Haryono and road HME AH.Nasution Mokodompit with approximately about 13.7 hectares of area. Land settlement has also increased due to the presence of the university as more and more people, especially students who need housing. The settlement of the land is 135.3 hectares. If the comparison between 2006 to 2010 trade and service area in 2006 is equal to 5.9 ha to 13.7 ha, while for the settlement of 104.3 hectares of land in 2006 to 135.3 ha. After analysis, we can conclude that the great land of each system can be said that the activities of approximately 15.34% of land settlements, trade and service area of about 1.10%, recreational land approximately 0.062% and 0.39% of the land area. Distribution of each system activity occupies two villages namely Lalolara Village and Village Kambu where development activity reached a radius of approximately 2 km from the University of Haluoleo. As can be recommended through this research that is aimed at community and government. Recommendations for the community itself is the need for public awareness, especially for business people to build businesses with the proper conditions to make it look organized and the anticipation for the community, especially for business people to deal with things like theft and others. while the government is the existence of government regulations on building permits so that trade and services appear more regularly and the structuring of economic activity, especially along the road Mokodompit HME. Some of these recommendations purposed for the influence or impact caused by land use changes due to developments in economic activity caused by the presence of Haluoleo University.